Study on the extraction of high methoxyl pectin from dragon fruit (hylocereus polyrhizus) peels and its adsorption performance againts cholesterol - Rubaiyi, Mat Zaid (2019)
Pectin is a high value soluble dietary fiber which is beneficial to health. Requirement to manufacture the high yield of pectin with certain characteristic is a major challenge. Pectin characteristic is the keywords to its application. The purpose of this study is to investigate the extraction of hydrophobic polysaccharide which is known as high methoxyl pectin extracted from Hylocereus polyrhizus peels as potential hypolipidemic agents by in vitro sorption experiments on model molecules (cholesterol). In this study, combination of physical and chemical treatment has been applied in the extraction process. Mild ultrasonic by sonicator bath and agitation by propeller with citric acid as an extraction solvent was employed in the extraction process to achieve the high yield of high methoxyl pectin. A study on the extraction parameters (agitation rate, temperature, time, pH and liquid-solid ratio (LSR)) was performed by one-factor-at-a-time (OFAT) to facilitate the appropriate range for further optimization process. The extraction process kinetics has been done after OFAT study which would give the idea for process forecasting and optimization of the pectin yield. The kinetic analysis by Panchev’s model shows that the extraction rate was found highest at LSR 10 v/w with ymax 30.85 %. The calculated activation energy for pectin dissolution and degradation was found to be 4.532 kJ/mol and 28.054 kJ/mol, respectively. The initial screening using 25 full factorial design indicated that temperature, time, pH and LSR were significant factors in the extraction of high yield of high methoxyl pectin. All the significant factors were then optimized using response surface methodology (RSM) to achieve the high yield of high methoxyl pectin. The value of pectin yield and degree of esterification (DE) after optimization were 30.11 % and 55.00 %, respectively as compared to the initial pectin yield and DE of 21.52 % and 56.1 %, respectively. High methoxyl pectin extracted from Hylocereus polyrhizus peels (HMPHPP) were tested as potential cholesterol-lowering agent and compared with the commercial high methoxyl citrus pectin (HMPCP). The cholesterol sorption was measured quantitatively by high performance liquid chromatography (HPLC). It was found that high methoxyl pectin from Hylocereus polyrhizus peels has the affinity towards cholesterol which followed the Freundlich isotherm and pseudo-first order model. Hydrophobicity and surface structure of the HPP was characterized by contact angle analysis and field emission scanning electron microscopy (FESEM) in order understand HMPHPP surface that help the adsorption process. This study proves that high methoxyl pectin extracted from Hylocereus polyrhizus peels has affinity towards cholesterol which help the adsorption of cholesterol.